Slot-die coating of hybrid perovskite : material study and integration into photovoltaic devices - Fievez, Mathilde (Nanyang Technological University, 2021)
In the last decade, metal halide perovskites have emerged as an innovative thin film photovoltaic technology that contrasts with current technologies due to its solution processability that could significantly reduce its manufacturing environmental footprint. In 2020, perovskite solar cells at laboratory scale reach 25.5% power conversion efficiency, closing the gap to silicon based solar cells performances (26.6%). One of the major bottlenecks of perovskite photovoltaic modules fabrication is the homogeneous deposition of perovskite material over large areas. Whereas scalable processes (inkjet, slot-die coating) can be adapted from the organic photovoltaics industry to deposit the wet precursor film over large areas, the control of the perovskite crystallization remains a challenge at that scale. In this work, we investigate the wet deposition of double cation mixed-halides perovskite (CsxFA(1-x)Pb(I0.88Br0.12)3) via slot-die coating combined with synergistic gas quenching and substrate heating over 5 x 5 cm2 and 10 x 10 cm2 substrates. More specifically, we detail the effect of the process parameters, precursor ink composition and substrate nature (e.g. planar vs mesoporous, TiO2 vs SnO2) on the perovskite film morphological and opto-electronics properties. We unveil the role of the CsI precursor in the gas-assisted crystallization and show that its effect differs from the conventional anti-solvent assisted crystallization. We show that slot-die coating technique combined with synergistic gas quenching and substrate heating can produce compact, homogenous and reproducible Cs0.15FA0.79Pb(I0.88Br0.12)3 perovskite films. We integrate the perovskite slot-die coated layers in planar (n-i-p) photovoltaic device configuration yielding power conversion efficiency (PCE) of 18% over 0.09 cm2 and 11.5% over 52 cm2 device active area. This work provides insights into achieving controlled perovskite crystallization of perovskite films over large areas, which is necessary for the industrialization of this technology.